The Comprehensive Evaluation of Reclaimed Water Effectively Utilization Policy in Tianjin, China - Nan XIANG; Feng XU; Shanshan WANG; Yang LI; Takeshi MIZUNOYA; Yabar HELMUT (European Regional Science Association (ERSA), 2011)
Increasing scarcity of freshwater resources and growing environmental awareness give rise to the use of reclaimed wastewater as an additional source of water supply. However, the amount of wastewater that can be reclaimed for reuse is subject to many factors, ranging from technical possibility to socio-economic and institutional conditions. Taking Tianjin in China as a case study, this paper provides a systematic framework for the analysis of waste water reuse potential under various driving forces and constrains. A linear programming model was used to analyze reclaimed wastewater reuse potential and the different reuse scenarios concerning environmental and economic development. In this paper we propose tentative policy proposals for meeting such challenges for economic development, water saving and water quality perfection. Through simulation and evaluation of introducing new advanced technologies and sewage plant in the catchment area, the simulation results suggest that the wastewater reuse can substitute 16 percent of freshwater under rational economic, financial and environmental constraints. The framework established in this study and the results of Tianjin case study help to give the optimal policy proposals of reclaimed water utilization. This study also provides a useful basis for the evaluation of specific wastewater reuse simulation for further research.
Keywords: 330